Cajun night before Christmas - Trosclair; Jacobs, Howard; Rice, James, 1934- (Gretna [La.] Pelican Pub. Co., 1973)
A version in Cajun dialect of the famous poem, "The Night Before Christmas," set in a Louisiana bayou.
Keywords: Children$1 (Bs poetry, American.s; Santa Claus -- Juvenile poetry; Christmas -- Juvenile poetry; Cajuns -- Juvenile poetry; Christmas -- Poetry; Santa Claus -- Poetry; American poetry